2019
DOI: 10.1158/2326-6066.cir-18-0419
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T Cells in an Endogenous Mouse Lymphoma Recognize Specific Antigen Peptides and Contribute to Immune Escape

Abstract: Foxp3 þ regulatory T cells (Tregs) sustain immune homeostasis and may contribute to immune escape in malignant disease. As a prerequisite for developing immunologic approaches in cancer therapy, it is necessary to understand the ontogeny and the antigenic specificities of tumor-infiltrating Tregs. We addressed this question by using a l-MYC transgenic mouse model of endogenously arising B-cell lymphoma, which mirrors key features of human Burkitt lymphoma. We show that Foxp3 þ Tregs suppress antitumor response… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…We detected no CD8 + T cells and no CD49b + NK cells ( Supplementary Fig. 6d), what may be due to the fact that NK cells are primarily found in the spleen 40,41 . As ICB induced a similar immune infiltrate in RT2cancers and in Stat1-and Cdkn2a-deficient RT2-cancers ( Supplementary Fig.…”
Section: Weeks Of Treatmentmentioning
confidence: 88%
See 1 more Smart Citation
“…We detected no CD8 + T cells and no CD49b + NK cells ( Supplementary Fig. 6d), what may be due to the fact that NK cells are primarily found in the spleen 40,41 . As ICB induced a similar immune infiltrate in RT2cancers and in Stat1-and Cdkn2a-deficient RT2-cancers ( Supplementary Fig.…”
Section: Weeks Of Treatmentmentioning
confidence: 88%
“…Lymphoma-specific, regulatory T cells are also increased in the spleen. Yet, depletion of regulatory T cells delays lymphoma development and death only for a short time 40 .…”
Section: Weeks Of Treatmentmentioning
confidence: 99%
“…Ablation of Foxp3 + Tregs significantly delayed tumour development. The ratio of Tregs to effector T cells was elevated in growing tumours [ 136 ]. The infiltration of T cells into the TME represents a critical bottleneck for immune-mediated control of cancer.…”
Section: Tumour Immunotherapy Strategies Targeting Tregsmentioning
confidence: 99%
“…However, MHC class II-restricted antigen presentation may not always have positive effects on antitumor immunity. A study in mice found that nonmutated self-epitopes that might be overexpressed in tumor cells could be presented by MHC class II and be recognized by Tregs, which could suppress the antitumor response of the host 30. Another study showed that the antigen presented by tumor cells through MHC class II could alter tumor antigen specific T cells into Tregs and restrict the ability to eliminate tumor cells 31…”
Section: Mhc Class II In Antitumor Immunitymentioning
confidence: 99%